Pengaruh Harga Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Jasa Ekspedisi JNE Cabang Bogor - Irawan, Rayhan Diki; Senen (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to determine how much Price Influences the Decision to Purchase Services on JNE Expeditions in Bogor, to determine how much Service Quality Influences the Decision to Purchase Services on JNE Expeditions in Bogor, to determine how much Price and Service Quality Influences the Decision to Purchase Services on JNE Expeditions in Bogor. This study uses a quantitative approach with a research sample of 99 respondents and probability sampling techniques, as well as data collection techniques through questionnaire distribution. The data analysis methods used are data instrument tests, classical assumption tests, simple and multiple linear regression tests, coefficient of determination and hypothesis testing. The results of the study indicate that Price (X1) and Service Quality (X2) have a significant effect on Purchase Decisions (Y) with the regression equation Y = 0.778 + 0.657 X1 + 0.371 X2. The correlation value of 0.921 means that the independent variable with the dependent variable has a very strong relationship. The coefficient of determination value is 84.7% while the remaining 15.3% is influenced by other factors. Hypothesis test obtained F count value > F table or (266.622 > 3.09). Thus H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence of Price and Service Quality on Purchase Decisions for JNE Expedition Services in Bogor.